2020
DOI: 10.1101/2020.01.24.919316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiota Mediates the Protective Effects of Andrographolide Inhibits Inflammation and Nonalcoholic Fatty Liver Disease(NAFLD) in High-Fat Diet induced ApoE(-/-) Mice

Abstract: Mechanisms relating the gut bacteria to Nonalcoholic Fatty Liver Disease (NAFLD) have been proposed containing the dysbiosis-induced dysregulation of hepatic lipid metabolism that allows for the translocation of microbial components and leads to hepatic inflammation and steatosis. Andrographolide (AG) regulates inflammation mediated by NF-κB pathway which also play a key role in reduction of inflammation and fibrosis in experimental nonalcoholic steatohepatitis (NASH), yet the mechanisms linking this effect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The transcriptome analysis showed that WPI reduced the inflammatory response in the hypothalamus, liver, and jejunum, whereupon improvements in insulin and IGF-1 receptor signaling (in the hypothalamus) occurred, alongside downregulation of the PTPRJ (PTP receptor type J) pathway and recoupling of the GH and IGF-1 axis. Moreover, WPI protected intestinal integrity during high-fat feeding by upregulation of genes encoded junctional proteins, Ptpn22 and the IL-10RA regulator known to be involved in maintenance of intestinal integrity and homeostasis (Spalinger et al, 2015) and by increased production of andrographolide in the cecum, which is known to improve intestinal permeability and mucosal architecture and reduce NAFLD (non-alcoholic fatty liver disease) (Shi et al, 2020). These effects were further supported by inhibition of LPS-and MYD88-related transcriptome signaling, linked to reduced liver fat accumulation and inflammation (Cani et al, 2008), reduced plasma TNF-a/CCL2 levels, and reduced NF-kB and LPS/TLR4 activation in tissues (Ahmad et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome analysis showed that WPI reduced the inflammatory response in the hypothalamus, liver, and jejunum, whereupon improvements in insulin and IGF-1 receptor signaling (in the hypothalamus) occurred, alongside downregulation of the PTPRJ (PTP receptor type J) pathway and recoupling of the GH and IGF-1 axis. Moreover, WPI protected intestinal integrity during high-fat feeding by upregulation of genes encoded junctional proteins, Ptpn22 and the IL-10RA regulator known to be involved in maintenance of intestinal integrity and homeostasis (Spalinger et al, 2015) and by increased production of andrographolide in the cecum, which is known to improve intestinal permeability and mucosal architecture and reduce NAFLD (non-alcoholic fatty liver disease) (Shi et al, 2020). These effects were further supported by inhibition of LPS-and MYD88-related transcriptome signaling, linked to reduced liver fat accumulation and inflammation (Cani et al, 2008), reduced plasma TNF-a/CCL2 levels, and reduced NF-kB and LPS/TLR4 activation in tissues (Ahmad et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Bacteroides are beneficial for the immune system [ 31 ]. Shi et al [ 32 ] found that an increased abundance of Faecalibaculum improved fatty liver in atherosclerosis model mice, indicating its potential hepatoprotective function. Our study showed that camellia oil significantly increased the abundance of Faecalibaculum in the intestinal flora and significantly reduced the accumulation of hepatic TG and TC in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Only HpT2 enhanced the abundances of Faecalibaculum and Ileibacterium to the levels in the Con group. In a previous study, andrographolide was used to regulate non-alcoholic fatty liver disease and was shown to decrease the relative abundance of Bacteroides while increasing the abundances of Faecalibaculum and Akkermansia ( Shi et al, 2020 ). Importantly, Faecalibaculum , Bacteroides and Akkermansia appeared to be closely related to the recovery of non-alcoholic fatty liver disease and alteration of gut microbiota in hyperlipidemia ( Ma et al, 2019 ; He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%